Lucha interior/ imagen exterior: Escindido discurso teatral feminista en La colección de relojes de Renée Ferrer y Casa de muñecas de Henrik Johan Ibsen - Whittingham, Georgina (Latin American Theatre Review, 2018)
Paraguayan author Renée Ferrer and Norwegian dramatist Henrik Ibsen are among the first writers to depict the rise of feminist consciousness in their respective countries. In Ibsen’s A Doll’s House (1879), the heroine’s restrictive economic and domestic role nearly destroys her sanity and shatters her marriage and its appearance of perfect bliss. Her distress is framed in the play’s suspenseful action and precise conversational speech, characteristic of nineteenth-century realist drama. La colección de relojes (2001), Renée Ferrer’s one-act play, takes place within the context of Alfredo Stroessner’s (1954-1989) repressive regime. Splintered interior monologues, the dramatic text’s predominant discourse, reflect the protagonist’s cultural subordination and anguished dependence on a loveless marriage. In contrast, her connection to plastic arts and music provides support in her continued struggle for emancipation. Basing my argument on the premise that sixteenth-century Spanish conduct manuals—models of age-old control mechanisms—produce compliant female bodies obedient to patriarchal norms, I maintain that the historical bias under which women have lived continues to affect their freedom. Women continue to suffer under largely invisible mental constructs and traditions originally designed to prevent them from holding public positions and keep them enclosed in the domestic sphere.